The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1128/iai.00349-19
|View full text |Cite
|
Sign up to set email alerts
|

DprA-Dependent Exit from the Competent State Regulates Multifaceted Streptococcus pneumoniae Virulence

Abstract: Streptococcus pneumoniae (pneumococcus) causes multiple infectious diseases. The pneumococcal competence system facilitates genetic transformation, spreads antibiotic resistance, and contributes to virulence. DNA-processing protein A (DprA) regulates the exit of pneumococcus from the competent state. Previously, we have shown that DprA is important in both bacteremia and pneumonia infections. Here, we examined the mechanisms of virulence attenuation in a ΔdprA mutant. Compared to the parental wild-type D39, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…We used the serotype 2 strain D39 to construct the reporter strain AD2501 harboring a firefly luciferase transcriptionally fused to the ssbB gene (D39-ssbB-luc; Fig. 1A) (29). The ssbB gene encodes a single-stranded DNAbinding protein and is uniquely induced during competence induction and directly protects internalized single-stranded DNA (30).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We used the serotype 2 strain D39 to construct the reporter strain AD2501 harboring a firefly luciferase transcriptionally fused to the ssbB gene (D39-ssbB-luc; Fig. 1A) (29). The ssbB gene encodes a single-stranded DNAbinding protein and is uniquely induced during competence induction and directly protects internalized single-stranded DNA (30).…”
Section: Resultsmentioning
confidence: 99%
“…For example, we found that D39 was not able to enter the competent state spontaneously when cultured in the nutrient-rich THY medium most widely used to cultivate pneumococci ( Fig. 1) (29). The competence-permissible CϩY medium, which contains defined amino acids, bovine serum albumin (BSA), and other nutrients, was formulated based on early findings that BSA or bodily fluids, including peritoneal washings and blood, provided better conditions for competence induction (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…sobrinus is one of the few species of oral streptococci that lack a natural competence pathway. Competence is central to pathogenicity in streptococci, and competence pathways are connected to metabolism [4], virulence [5,6], quorum sensing [7], and antibiotic tolerance [8]. The natural competence of streptococci has been known for over 75 years [9].…”
Section: Introductionmentioning
confidence: 99%